KINETICS OF OXIDATIVE CHLORINATION OF METHANE - I. S. Silina; Е. А. Katsman; Yu. A. Treger; V. N. Rozanov; L. D. Iskhakova; R. P. Ermakov; V. V. Koltashev; L. G. Bruk (Тонкие химические технологии, 2017)
Heterogeneous oxidative chlorination of methane was investigated. The target product is methyl chloride. The investigated terms and conditions of oxychlorination of methane: process temperature 400°C, pressure 0.1-0.9 MPa, catalyst (% weight.): copper chloride (II) 1-8%; potassium chloride 2.5%; lanthanum chloride 1%; carrier - aluminosilicate. Powder X-ray diffractometry and electron microscopy showed that the active catalyst components (CuCl2, KCl, LaCl3) are unevenly distributed on the support surface (α-Al2O3·SiO2) and form agglomerates with a high salt content, including binary chlorides such as KCuCl3, K2CuCl3 or K2CuCl4, hydrates K2CuCl4·2H2O and CuCl2·2H2O and hydroxychlorides Cu3Cl4(OH)2 and Cu2Cl(OH)3. The kinetics of methane oxychlorination was studied in a gradientless reactor at 400°C and pressure 0.1 - 0.9 MPa by varying the partial pressures of the reactants. Analysis of the products was carried out by GC. An equation of the reaction rate including partial pressures of methane, hydrogen chloride and water to the 0.77, 0.01 and 0.64 power, respectively, but of zero order by oxygen and chlorine provides an adequate description of methyl chloride formation rate. Significant influence of water partial pressure is proved for the reaction under consideration.